2016
DOI: 10.1074/jbc.m115.686295
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin on the Surface of Myeloma Cell-derived Exosomes Mediates Exosome-Cell Interactions

Abstract: Exosomes regulate cell behavior by binding to and delivering their cargo to target cells; however, the mechanisms mediating exosome-cell interactions are poorly understood. Heparan sulfates on target cell surfaces can act as receptors for exosome uptake, but the ligand for heparan sulfate on exosomes has not been identified. Using exosomes isolated from myeloma cell lines and from myeloma patients, we identify exosomal fibronectin as a key heparan sulfate-binding ligand and mediator of exosome-cell interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
232
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(244 citation statements)
references
References 41 publications
11
232
0
1
Order By: Relevance
“…48,49 Our findings also show that both resting or IL-15 activated primary NK cells internalize, and not only bind MM cell-derived exosomes with a rapid kinetics. Interestingly, we found that NK cell exosome uptake is an active process that mainly depends on endocytic route/s requiring dynamin and caveolae/raft endocytosis ( Fig.…”
Section: Discussionsupporting
confidence: 62%
“…48,49 Our findings also show that both resting or IL-15 activated primary NK cells internalize, and not only bind MM cell-derived exosomes with a rapid kinetics. Interestingly, we found that NK cell exosome uptake is an active process that mainly depends on endocytic route/s requiring dynamin and caveolae/raft endocytosis ( Fig.…”
Section: Discussionsupporting
confidence: 62%
“…These EVs have an outer coating of fibronectin which is bound to the EVs through integrin α5. This fibronectin coat facilitates the interaction between the EVs and target cells through heparan sulfate (Purushothaman, Bandari et al 2016). These fibronectin-containing EVs may anchor themselves to both the cancer cell and the endothelial wall, allowing for the cancer cell to undergo directional migration on the inner surface of blood vessels (Fig.…”
Section: Delivery To Thy Neighbor: Communication Within the Primary Tmentioning
confidence: 99%
“…Integrins have also been shown to act as EV receptors by binding lysophosphatidic acid from the EV surface [32]. Furthermore, heparan sulphate proteoglycans (HSPGs) on the plasma membrane were reported to function as EV receptors, in a mechanism in which fibronectin acts as a bridging molecule that interacts with both cellular and exosomal HSPGs [33,34]. …”
Section: Introductionmentioning
confidence: 99%